Changes in the interpersonal relationships of young university students during the pandemic (2021)
Over the past year, many of the things that were part of daily life such as studying and working changed because of the pandemic. Another aspect that changed was avoiding contact with others to try and avoid the spread of the new disease as well as stay healthy. This study identified the changes that occurred in friendships, love, family, and working relationships of young university students during the quarantine period in Colombia, due to Covid-19. From a chain sampling, the participation of 194 people was obtained. It was found that the relationship that changed the most for young university students was that of friendship. Likewise, some gender differences were evidenced in the relationships of couples, fear of infection during gatherings and meetings, and expressions of affection, such as greeting close friends. m.